Extracorporeal Membrane Oxygenation for Adult Patients With Neoplasms: Outcomes and Trend Over the Last 2 Decades. Issue 2 (12th April 2022) - Suzuki, Yota; Mobli, Keyan; Cass, Samuel H.; Silva, Madeline M.; DeAnda, Abe; Tyler, Douglas S.; Radhakrishnan, Ravi S.
Abstract : Extracorporeal membrane oxygenation (ECMO) is utilized in the management of severe respiratory and circulatory failure. Advanced malignancy is a relative contraindication, but the indication for ECMO in the oncologic population has not been clearly established because of the wide spectrum of malignant disease and prognoses. The Extracorporeal Life Support Organization database was queried for patients older than 18 years with an International Classification of Diseases code of neoplasm over the past 2 decades (2000–2019). The data were divided into 2 decades to analyze and compare the trends with background and outcomes. One thousand six-hundred ninety-seven patients met inclusion criteria from the latest decade which is over 15 times the previous decade (n = 110). Compared with the previous decade, ECMO was used more in patients with older age (56 vs . 50.5 years old; p < 0.001), cardiac and extracorporeal cardiopulmonary resuscitation (ECPR) support type ( p = 0.011), and lower oxygenation index (23.0 vs . 35.6; p < 0.001) in the latest decade. Although overall survival did not show significant improvement overall (38.9% vs . 33.6%; p = 0.312), survival in pulmonary ECMO has significantly improved in the latest decade (41.6% vs . 29.1%; p = 0.032). Compared with the previously reported data for all adult ECMO, our patients had a significantly lower survival with pulmonary (41.6% vs . 61.1%; p < 0.001) and cardiac (38.4% vs . 44.3%; p = 0.008) support while not with ECPR.